Estimating reservoir sedimentation using bathymetric differencing and hydrologic modeling in data scarce Koga watershed, Upper Blue Nile - Mhiret, Demesew Alemaw; Ayana, Essayas K.; Legesse, Elias S.; Moges, Michael M.; Tilahun, Seifu A.; Moges, Mamaru A. (Journal of Agriculture and Environment for International Development (JAEID), 2016)
ABSTRACT Modeling sediment accumulation in constructed reservoirs is hampered by lack of historic sediment concentration data in developing countries. Existing models simulate sediment concentration using data generated from sediment rating curves usually defined as a power function of the form S = aQb This often results in residual errors that are not identically distributed throughout the range of stream flow values adding to uncertainty in sediment modeling practices. This research measure accumulated sediment in Koga dam in the upper Blue Nile Basin and use the result to validate a Soil and Water Assessment Tool (SWAT) sediment model that uses sediment data from rating curves. Bathymetric differencing of the original and current storage digital elevation models (DEMs) indicate that the sediment was accumulating at a rate of 5 ton/ha/year while a calibrated SWAT model resulted in 8.6 ton/ha/year. Given the complicated sediment transport processes that are not fully understood and comparable rates reported in recent studies these results are satisfactory. Keywords: Reservoir sedimentation, Koga reservoir, bathymetry